1988
DOI: 10.1128/iai.56.4.802-807.1988
|View full text |Cite
|
Sign up to set email alerts
|

Steric hindrance of antibody binding to surface proteins of Coxiella burnetti by phase I lipopolysaccharide

Abstract: The exposure of surface protein antigens on virulent phase I Coxiella burnetti was compared with that on avirulent phase II cells. Although anti-phase II antibodies did not bind to the surfaces of native intact phase I cells, they bound to phase I proteins if the proteins were solubilized for sodium dodecyl sulfate-polyacrylamide gel electrophoresis and analyzed by immunoblotting. In addition, removal of the phase I lipopolysaccharide (LPS) by trichloroacetic acid exposed surface proteins for reactivity with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

1989
1989
2019
2019

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 29 publications
0
21
0
2
Order By: Relevance
“…Hindrance of antibody access has been noted in other pathogens. In gram-negative bacteria, such as Neisseria gonorrhoeae, E. coli, and Brucella spp., lipooligosaccharides or lipopolysaccharides shield porin proteins from antibody (21,29,60). B. burgdorferi lacks these molecules (59) but instead expresses abundant Osp proteins that appear to hinder the access to other outer membrane proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Hindrance of antibody access has been noted in other pathogens. In gram-negative bacteria, such as Neisseria gonorrhoeae, E. coli, and Brucella spp., lipooligosaccharides or lipopolysaccharides shield porin proteins from antibody (21,29,60). B. burgdorferi lacks these molecules (59) but instead expresses abundant Osp proteins that appear to hinder the access to other outer membrane proteins.…”
Section: Discussionmentioning
confidence: 99%
“…First, it has been shown that the Intracellular bacterium Coxiella burnetti undergoes a phase variation in which the highly virulent Phase I organism has very large amounts of LPS on its surface. Antibody raised against bacteria growing in the second (less virulent) phase cannot recognize proteins on the surface of the Phase I organism because of steric hindrance by LPS (Hackstadt, 1988). Inasmuch as antibody is able to recognize Jnvasin on the surface of Shigella.…”
Section: Discussionmentioning
confidence: 99%
“…burnetii displays antigenic variations similar to the smooth-rough variation in the family Enterobacteriaceae. Phase variation is related mainly to mutational variation in the lipopolysaccharide (LPS) (129)(130)(131). Phase I is the natural phase found in infected animals, arthropods, or humans.…”
Section: Bacteriologymentioning
confidence: 99%